1998
DOI: 10.1021/ic971194v
|View full text |Cite
|
Sign up to set email alerts
|

A 1H NMR Study of the DNA Binding of Ruthenium(II) Polypyridyl Complexes

Abstract: 1H NMR spectroscopy was used to study the oligonucleotide binding of the Δ enantiomers of [Ru(phen)2L]2+ where the bidentate ligand L is 1,10-phenanthroline (phen), dipyrido[3,2-d:2‘,3‘-f]quinoxaline (dpq) or dipyrido[3,2-a:2‘,3‘-c](6,7,8,9-tetrahydro)phenazine (dpqC). The data from one- and two-dimensional NMR experiments of the oligonucleotide−metal complex binding suggest that all three ruthenium(II) polypyridyl complexes bind in the DNA minor groove. While a minimally intercalated oligonucleotide binding m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
237
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 315 publications
(253 citation statements)
references
References 38 publications
15
237
1
Order By: Relevance
“…The ligand dipyrido-[3,2-d:2 0 ,3 0 -f]-quinoxaline was synthesized by Hambly et al [34]. Ultrapure Milli Q water (18.3 lX) was used for all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The ligand dipyrido-[3,2-d:2 0 ,3 0 -f]-quinoxaline was synthesized by Hambly et al [34]. Ultrapure Milli Q water (18.3 lX) was used for all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…When ESI mass spectra were acquired in positive ion mode (Figures 6a and b), there were no significant ions present from any dsDNAdrug complex in any of the mixtures; the only ions observed were from free D3 or single strands from D3. In contrast, the negative ion spectra (Figures 6c and d) showed ions from dsDNA-drug complexes with the number of drug molecules bound to DNA increasing with increasing amounts of [Ru(phen) 2 Since DNA is negatively charged in solution and these Ru-based compounds have been shown to bind to DNA using other techniques [23], the negative ion spectra are likely to provide a more accurate picture of the complexes present in solution. Furthermore, previously it has been shown that complexes of well-characterized intercalators with dsDNA can be detected in positive and negative ion ESI mass spectra [6,14].…”
Section: Binding Of Ru-based Intercalators To Dsdnamentioning
confidence: 97%
“…NMR studies show that these ligands intercalate between DNA base pairs [23]. In the present work, we have focused on the interactions of [Ru(phen) 2 dpq]Cl 2 and [Ru(phen) 2 dpqC]Cl 2 with D3.…”
Section: Binding Of Ru-based Intercalators To Dsdnamentioning
confidence: 99%
See 1 more Smart Citation
“…The basic structures consist of a Ru(II) surrounded by three heterocyclic, aromatic ligands. [84][85][86] Specific structures include Ru(phen) 3 2+ and Ru(bpy) 2 dppz 2+ . Recent AFM studies have determined the binding constant of Ru(bpy) 2 dppz 2+ to be (1.5 6 0.7) Â 10 5 M À1,28 by examining the length of the DNA as a function of ligand concentration.…”
Section: Ruthenium Complexes Studied With Tweezers and Afmmentioning
confidence: 99%